2005
DOI: 10.1097/01.mlg.0000177034.51559.50
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine and Microsurgery Induced Recovery of the Vocal Cord after Recurrent Laryngeal Nerve Resection

Abstract: Transection of the recurrent laryngeal nerve leads to permanent palsy of the vocal cord. Experimental studies have confirmed that nimodipine increases the pace of axonal regeneration. We present a case of a 19-year-old male, suffering a thyroid cancer disease, who was subjected to unilateral resection of the recurrent laryngeal nerve during surgery. The nerve was repaired with a nerve graft and the patient further treated with nimodipine for 3 months. Evaluation of the patient showed normalization of voice, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 7 publications
2
41
0
1
Order By: Relevance
“…2,20,21,24,25 Furthermore, these positive results were also observed in laryngeal 8,14 and maxillofacial surgery 23 and may therefore be transferable to other surgical procedures with nerves at risk.…”
Section: Generalizabilitymentioning
confidence: 74%
See 2 more Smart Citations
“…2,20,21,24,25 Furthermore, these positive results were also observed in laryngeal 8,14 and maxillofacial surgery 23 and may therefore be transferable to other surgical procedures with nerves at risk.…”
Section: Generalizabilitymentioning
confidence: 74%
“…The beneficial effect of nimodipine treatment for the protection and regeneration of the facial and cochlear nerves is supported by animal experiments 1,6,8,9,[12][13][14][15] and clinical trials in VS surgery. 2,20,21,24,25 Furthermore, these positive results were also observed in laryngeal 8,14 and maxillofacial surgery 23 and may therefore be transferable to other surgical procedures with nerves at risk.…”
Section: Generalizabilitymentioning
confidence: 86%
See 1 more Smart Citation
“…Patients with disfiguring palsy (HB >IV)28 showed significantly better results and retained long term socially acceptable facial nerve function in 80% compared with 65% in untreated patients 22. Clinical observations such as delayed facial nerve palsy following termination of vasoactive treatment29 or isolated case reports with successful recovery of recurrent laryngeal nerve function under nimodipine30 indicate a neuroprotective effect of calcium channel blockers.…”
Section: Discussionmentioning
confidence: 98%
“…Because no previous reports of RLN reconstruction in the thoracic field have been published, our experiences could shed light on intraoperative nerve repair and therefore reduce the rate of postoperative complications for patients with RLN injury. A previous report showed that nimodipine associated with microsurgery could induce vocal cord recovery after RLN resection in thyroid surgery 10. Another study showed satisfactory vocal cord recovery after immediate RLN reconstruction in thyroid cancer patients 3.…”
Section: Discussionmentioning
confidence: 97%